Social and marketing issues in works by M.I. Tugan-Baranovsky (from his publication “Social foundations of cooperation”) - Антоненко, Леонид Анисимович; Фролова, Марина (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article contains theoretical and methodological conclusions pertaining to the development of cooperatives inUkraine, based on pre-revolutionary publications on developing cooperatives inEnglandand other Western countries. Special attention is paid to the social and marketing peculiarities of specialized cooperatives’ operation as an alternative to the unwarranted expansion of intermediary and merchant bodies in the current Ukrainian economy. This is based on M.I. Tugan-Baranovsky’s detailed personal analysis of the classification of cooperatives. His conclusions and proposals are aimed at perfecting the macroeconomic preconditions of stable development without intermediaries between a product’s manufacturer and its end-users.